DIFERENSIASI DALAM KEUNGGULAN BERSAING PERUSAHAAN - Aprinawati; Daniel Bintang Tambunan; Geana Syah Putri Br Lubis; Rexa Ananda Sufi; Rita Ramadhani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
A strategy is required by the competitive environment, and having the right plan is necessary to win the competition. indicates that the objective of creating a competitive strategy is to integrate the organization with its environment. The industry or industries in which the firm competes is the main part of its environment, even though the relevant environment is very broad and consists of both social and economic factors. Having a sustained competitive edge is essential for organizations to attain profitability above industry average. These strategies are called generic strategies. The three strategies that make up the strategy are the differentiation strategy, the cost leadership strategy, and the focus strategy (which can be either differentiation or cost leadership). The differentiation strategy used by a corporation to gain a competitive advantage is the main topic of this essay. By realizing the value of differentiation strategy, businesses may set themselves apart from the competition and succeed in a market where competition is fiercer than ever. Businesses that already set themselves apart from rivals can benefit from this research by being able to highlight and explain those distinctions more effectively.